A Novel Energy Management Technique for Shared Solar and Storage Resources in Remote Communities - Mumbere, Samuel Kihembo; Tanioka, Yoshiki; Matsumoto, Soichiro; Fukuhara, Atsushi; Sasaki, Yutaka (IEEE, 2020)
World over, the cost of PV equipment continues to decrease. Coupled with their quick time to install and the advancement of renewables in the face of climate change; they are fast becoming an appealing solution for remote communities that still have no access to national grids. In this paper, we study management of the state of charge (SOC) of batteries in an off-grid situation where multiple prosumer installations in different areas are interconnected to a shared distribution line. Each distinct installation consists of Photovoltaic power generation (PV), Storage batteries (BT), converters, their connection line DC power bus, and AC loads connected via an inverter, all modeled MATLAB / Simulink Simscape Power Systems. We develop a tool for improving BT utilization, monitoring, and managing energy consumption while maintaining the voltage at acceptable levels. Considering Uganda as an example, our research suggests a solution for electrifying remote communities by installing shared solar and storage units.
Keywords: Novel Energy Management Technique; Shared Solar and Storage Resources; Remote Communities